Strengthening Community Legal Literacy on Land Boundaries and Land Rights in Saragi Village - L.M. Ricard Zeldi Putra; Samsul; Wa Ode Novita Ayu Muthmainna; Jufri; Alimato (Permadani: Jurnal Pengabdian Riset Masyarakat Madani, 2025)
This community service article reports the implementation and outcomes of a program entitled “Strengthening Community Legal Literacy on Land Boundaries and Land Rights in Saragi Subdistrict.” The program was developed in response to recurring community challenges related to unclear land boundaries, weak documentation, and limited understanding of land rights and administrative procedures, which may escalate into prolonged disputes and social tension. The main objective was to improve residents’ legal literacy and practical capacity to prevent and manage land boundary issues in an orderly and peaceful manner. The program employed a participatory educational approach consisting of three phases: preparation, core implementation, and evaluation with follow-up. During the preparation phase, coordination with the subdistrict office, neighborhood leaders (RT/RW), and community figures was conducted to map common problems and tailor the content to local needs. The core implementation involved three main activities: (1) legal socialization and education on land boundaries, land rights, ownership evidence, and precautionary principles in transactions and inheritance; (2) practical boundary clarification training, including simulations of boundary marker placement, simple boundary sketch mapping, photo documentation, and drafting written boundary agreements (minutes) acknowledged by local authorities; and (3) a consultation clinic with light mediation support to guide residents in resolving boundary issues through structured deliberation before resorting to formal legal channels. Evaluation results indicated increased participant understanding of key land-law concepts, improved awareness of the importance of documentation and witnesses, and stronger readiness to apply preventive practices. The program also produced practical outputs, including document templates (boundary minutes and land-document checklists) and a recommended local contact point for ongoing guidance. Overall, the program demonstrates that integrating education, hands-on practice, and consultative support can strengthen community legal literacy, reduce dispute risks, and promote social harmony in land-related matters.